2012
DOI: 10.1128/jb.06457-11
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Stress Resistance in Porphyromonas gingivalis Is Mediated by a Putative Hydroxylamine Reductase

Abstract: bPorphyromonas gingivalis, the causative agent of adult periodontitis, must maintain nitric oxide (NO) homeostasis and surmount nitric oxide stress from host immune responses or other oral bacteria to survive in the periodontal pocket. To determine the involvement of a putative hydroxylamine reductase (PG0893) and a putative nitrite reductase-related protein (PG2213) in P. gingivalis W83 NO stress resistance, genes encoding those proteins were inactivated by allelic exchange mutagenesis. The isogenic mutants P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 63 publications
5
65
1
Order By: Relevance
“…Thus, it can survive the innate immune response, which is especially elevated in inflamed periodontal pockets. Our data verify the results recently reported by Boutrin et al (7), who have shown that P. gingivalis can grow in the presence of low nitric oxide concentrations.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Thus, it can survive the innate immune response, which is especially elevated in inflamed periodontal pockets. Our data verify the results recently reported by Boutrin et al (7), who have shown that P. gingivalis can grow in the presence of low nitric oxide concentrations.…”
Section: Discussionsupporting
confidence: 83%
“…The upregulation of hcp was quantified using qRT-PCR to be more than 150-fold higher upon exposure to nitrosative stress. This result is much higher than that observed in a previous study that used NONOate as a nitric oxide donor (7). Such significant upregulation of hcp is in agreement with previous reports demonstrating drastic upregulation of this gene in other anaerobic and facultatively anaerobic bacteria exposed to nitrite (26,46,48,56).…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…The so called hybrid cluster protein (Hcp) is found in many anaerobic or facultatively anaerobic bacteria, where it functions in response to nitrosative stress [217][218][219][220]. Hcp shares structural homology with anaerobic carbon monoxide dehydrogenases and contain two types of iron sulfur clusters; the first occurs as either a [2Fe-2S] or [4Fe-4S] cluster, while the second, socalled "hybrid cluster", is a unique cluster type, the precise form of which is dependent on the oxidation state.…”
Section: Hcpr2 and The Hybrid Cluster Protein (Hcp)mentioning
confidence: 99%